ANALISIS TERHADAP NILAI KEBARUAN INVENSI VIRTUAL PRESENTER ARTIFICIAL INTELLIGENCE MILIK INEWS MEDIA GROUP: Analysis of the Novelty Value of the Artificial Intelligence Virtual Presenter Invention Owned by iNews Media Group - Monnalysa Julyan Chairul; Aline Gratika Nugrahani (Faculty of Law, Universitas Trisakti, 2025)
The iNews Media Group, before submitting its invention to the Directorate General of Intellectual Property Rights, had already launched its invention, namely the Artificial Intelligence Virtual News Presenter in the form of a talk show titled